Experimental Study on Heat Storage Properties Comparison of Paraffin/Metal Foams Phase Change Material Composites - Ahmed, Waqar; Hussain, Abid; Shahid, Hanzla; Ali, Imran; Ali, Hafiz Muhammad (Journal of thermal science, 2024)
Heat storage properties of phase change materials (PCMs) are essential characteristics that perform a key role in thermal heat energy storage systems. The thermal properties of PCMs can be improved by developing metal foam/PCM composites. The addition of metal foam in PCMs has a significant effect on the thermal characteristics of PCMs. In this paper, the heat storage properties of two different metal foam/PCM composites were experimentally examined. The behavior of paraffin in metal foam (copper and iron-nickel)/paraffin composites concerning pure paraffin at a constant heat flux of 1000 W/m 2 in three directions simultaneously ( x , y , and z ) was studied. Paraffin was infiltrated into copper and iron-nickel foams to develop composite materials which resulted in enhancing the thermal conductivity of the paraffin. A comparative analysis is made on the heat storage properties of paraffin in copper and iron-nickel foams/paraffin composites. Inner temperature distribution during the phase transition process is experimentally evaluated. This comparison indicates that temperature uniformity in copper foam/paraffin composite is better than in iron-nickel foam/paraffin composite and pure paraffin at the same heat flux. Experimental results show that at heat flux of 1000 W/m 2 , the heat storage time for copper foam/paraffin composite is 20.63% of that of iron-nickel foam/paraffin composite.